‘Pokok Hari Nyalah’: Catatan Budaya (Lokal) dalam Membaca Perubahan Iklim (Global) - Nasution Pangeran P.P.A. (Antropologi Indonesia, 2013)
In the last decade, the issue of climate change phenomenon has been a serious debate for thepeople around the world. The impact of the climate change symptom can be felt or experiencedirectly by a societal group in any environment. The problems being experienced by the peoplerelated with the climate change phenomenon can be revealed by tracing their knowledge (culture) in understanding and predicting the circumstances of the environment; their perception about the environment which has been more unpredictable in the recent time; and the effort that were applied by them to face of the unpredictable circumstances of the environment. That would be represented how culture revealed the climate change was not only about the physical environment, but also the social-cultural phenomenon.Keywords: climate change, knowledge (culture), unpredictable environment, and social-culturalphenomenon